A secelction of case studies regarding the changes brought on by tourist traffic in the areas containing examples of preserved timber architectural heritage on the border between Poland and Ukraine - Podhalański А. (My University, 2015)
Carpathian tourist traffic has been developing in its various forms since the 1960's. At first it was unorganized, after the area of the Bieszczady Mountains became popular and the renewing of the interest in timber architectural monuments – it evolved from the setting up of boy and girl scout camps in the direction of qualified tourism. Cultural tourism became its final form. The tourist trails that have been set up, including a timber architecture trail, and the introduction of the preserved timber Eastern Orthodox churches onto the UNESCO World Heritage Site List were the causative factors in stimulating this change. Unique structures found their place as parts of the open air museums, while the museums themselves started to pursue new methods of exhibition and marketing in order to raise awareness of what they have to offer. Within the main cities of the micro-region, museums that provide good conditions for the exhibition of the most precious collections of paintings, icons, sculpture and effects of folk art, were set up. We can also observe a consequent revitalization of historical structures, performed under the watchful eye of the conservation authorities. The exhibition of the region's culture could be rounded out and become more dynamic with the introduction of the promotion of the domestic multi-cultural traditions which were so characteristic of the area of Galicja and its current borderland, especially concerning the culture of the Lemkos. Карпатський туристичний трафік (Польщі) розвивається в різних формах, починаючи з 1960-х років. Спочатку – неорганізований, пізніше став популярним у районі Бєщад і викликав оновлення інтересу до дерев’яних архітектурних пам’яток – туризм перетворився від організованих молодіжних таборів для хлопчиків і дівчат до кваліфікованого туризму. Культурний туризм став його остаточною формою. Створено туристичні стежки, зокрема слідами дерев’яної архітектури, а введення збережених дерев’яних православних церков до списку світової спадщини ЮНЕСКО спричинило стимулювання цих змін. Унікальні будівлі стали частиною музею під відкритим небом, водночас музеї самі почали застосовувати нові методи маркетингу та організовувати виставки для того, щоб підвищити обізнаність про те, що вони можуть запропонувати. У головних містах регіону, музеї забезпечили хороші умови для виставок найцінніших колекцій картин, ікон, скульптури й артефактів народного мистецтва. Таким чином, можна спостерігати послідовне пожвавлення історичних споруд, збереження яких було виконане під пильним оком влади. Експозиції культури регіону могли б бути цільнішими та динамічнішими зі запровадженням промування українських мультикультурних традицій, які були так характерні для регіону Галичини та його сьогоднішнього прикордоння, особливо щодо культури лемків.
Підбір тематичних досліджень стосовно змін, зумовлених туристичними потоками у районах, що містять приклади збереженої дерев’яної архітектурної спадщини, на прикордонні між Польщею та Україною
Keywords: heritage tourism; Carpathians; Lemko; спадщина туризм; Карпати; лемки